Biochemical, biological and structural properties of romidepsin (FK228) and its analogs as novel HDAC/PI3K dual inhibitors. Issue 2 (28th January 2015) - Saijo, Ken; Imamura, Jin; Narita, Koichi; Oda, Akifumi; Shimodaira, Hideki; Katoh, Tadashi; Ishioka, Chikashi
<x xml:space="preserve">Abstract</x> Romidepsin (FK228, depsipeptide) is a potent histone deacetylase (HDAC) inhibitor that has FDA approval for the treatment of cutaneous and peripheral T‐cell lymphomas. We have previously reported that FK228 and its analogs have an additional activity as phosphatidylinositol 3‐kinase (PI3K) inhibitors, and are defined as HDAC/PI3K dual inhibitors. Because a combination of an HDAC inhibitor and a PI3K inhibitor induces apoptosis in human cancer cells in a synergistic manner, development of an HDAC/PI3K dual inhibitor will provide an attractive novel drug for cancer therapy. Using structure‐based optimization of the analogs, FK‐A11 was identified as the most potent analog. FK‐A11 inhibited phosphorylation of AKT and accelerated histone acetylation at lower concentrations, resulting in stronger cytotoxic effects than FK228 and the other analogs in human cancer cells. In this study, we have characterized the biochemical, biological and structural properties of FK228 analogs as PI3K inhibitors. First, FK‐A11 is an ATP competitive PI3K inhibitor. Second, FK‐A11 is a pan‐p110 isoform inhibitor. Third, FK‐A11 selectively inhibits PI3K among 22 common cellular kinases. Fourth, conformational changes of FK228 analogs by reduction of an internal disulfide bond have no effect on PI3K inhibitory activity, unlike HDAC inhibitory activity. Finally, molecular modeling of PI3K‐FK228 analogs and analyses of the binding affinities identified the structure that defines potency for PI3K inhibitory activity. These results prove our concept that a series of FK228 analogs are HDAC/PI3K dual inhibitors. These findings should help in the development of FK228 analogs as novel HDAC/PI3K dual inhibitors.